Accrued Earnings and Growth: Implications for Future Profitability and Market Mispricing - Fairfield, Patricia M.; Whisenant, J. Scott; Yohn, Teri Lombardi (The Accounting Review, 2003)
Prior research reveals that the accrual component of profitability is less persistent than the cash flow component, and that investors fail to fully appreciate their differing implications for future profitability (Sloan 1996). However, accruals are a component of growth in net operating assets as well as a component of profitability. Just as we can disaggregate profitability into accruals and cash flows from operations, we can disaggregate growth in net operating assets into accruals and growth in long-term net operating assets. We find that, after controlling for current profitability, both components of growth in net operating assets—accruals and growth in long-term net operating assets—have equivalent negative associations with one-year-ahead return on assets. This result is consistent with conservative accounting and diminishing marginal returns on investments. We also find that, after controlling for current profitability, the market appears to equivalently overvalue accruals and growth in long-term net operating assets relative to their association with one-year-ahead ROA. Our evidence suggests that the accrual anomaly documented in Sloan (1996) is a special case of what could be viewed as a more general growth anomaly.